Upotreba mikrofiltrovanih u odnosu na samo disagregirane matične ćelije iz masnog tkiva u regenerativnoj medicini - Svolacchia, Fabiano; Svolacchia, Lorenzo (Scripta Medica, 2020)
Background: Clinical use of adult mesenchymal stem cells (MSCa) in medicine and regenerative surgery is constantly evolving. Adipose tissue-derived stem cells (ADSc) are capable of inducing the production of new extracellular matrix (ECM), deposition of new collagen and early revascularisation. Methods: Flow cytometry was performed for 2 mL of cell colonies harvested from adipose tissue (AT). Comparation has been made of AT disaggregated only and the same AT disaggregated and microfiltered at 50 μm, 100 μm and 200 μm. Signs of inflammation after dermo-epidermal regeneration session through the mesotherapy method were observed and compared. Results: Even after filtration, significant number of ADSc was collected. An increase in the size of the filter did not always translate into an increase in the number of cells that were found in the microfiltrate. In the non-filtered AT disaggregated in both cases, highest number of cells was found, as expected, but at the expense of more pronounced inflammation. Sampling with the 16 Gauge needle produces superior results compared to the cannula in all cases. Conclusion: With this method in medicine and regenerative surgery it will be easier to exploit the growth factors, mRNA, MicroRNA, lipids and bioactive peptides emitted in the MSCa signalling micro-vesicles as they are isolated from the inflammatory component.